Characterisation of operational amplifiers at cryogenic temperatures for space applications. (1st January 2013) - Johnson, Jared; Daly, Michael G.; Hiemstra, David M.
There is considerable interest in using commercial off-the-shelf (COTS) electronic components for space applications. These devices can provide many advantages for the development of space hardware. These advantages include: lower power consumption, better availability, superior performance and higher levels of integration. One significant performance parameter for devices is their lowest operational temperature. Extending the operational range of devices is important to decrease the amount of energy used to maintain their operating environment. Lower energy consumption enables their use in smaller instruments and spacecraft with low energy generation potential and/or low thermal mass. In this paper, we present the results of the testing of a variety of commercial operational amplifiers. CMOS, JFET and bipolar operational amplifiers were tested under cryogenic temperature conditions to determine their suitability for space applications. The performance characteristics studied were: offset voltage, total harmonic distortion (THD), change in open loop gain, and noise voltage.